2013
DOI: 10.1007/s00384-013-1717-6
|View full text |Cite
|
Sign up to set email alerts
|

Severe intestinal toxicity after stereotactic ablative radiotherapy for abdominopelvic malignancies

Abstract: Following three fractions of SABR, V(25) is a valuable predictor of severe IT. And SABR would be conducted with a treatment interval of at least 48 h if possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…Three patients had pre-SBRT gastroduodenal ulcer confirmed by esophagogastroduodenoscopy. We previously performed studies about severe gastroduodenal and intestinal toxicity after SBRT using 3 fractions for abdominopelvic malignancies and reported their results [ 37 , 38 ]. In the study about gastroduodenal toxicity, we suggested that Dmax is a valuable predictor of severe gastroduodenal tocivity.…”
Section: Discussionmentioning
confidence: 99%
“…Three patients had pre-SBRT gastroduodenal ulcer confirmed by esophagogastroduodenoscopy. We previously performed studies about severe gastroduodenal and intestinal toxicity after SBRT using 3 fractions for abdominopelvic malignancies and reported their results [ 37 , 38 ]. In the study about gastroduodenal toxicity, we suggested that Dmax is a valuable predictor of severe gastroduodenal tocivity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, because a prospective study controlling DVH parameters has not been undertaken until now, there is no definite conclusion about gastrointestinal dose tolerance. Based on extensive experience in administering SBRT to tumors located in the abdominopelvic site using three fractions, we have recently suggested dose constraints for the gastroduodenum and intestine . A D max of 35 Gy was associated with a 5% increase in the probability of the development of severe gastrointestinal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinic, higher dosed hRT is sometimes applied on consecutive days. However, it is often applied every other day or only twice per week, mostly because of safety concerns to achieve better normal tissue protection and to avoid treatment-induced adverse effects (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%